DEVELOPMENT OF STEM-BASED LKPD ASSISTED BY PHYPHOX ON CIRCULAR MOTION MATERIAL TO IMPROVE CRITICAL THINKING SKILLS - Sahlan, Sahlan; Hikmatiar, Hamzarudin; Amin, Chintia Nazilah (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to design and produce Student Activity Sheets based on the Science Technology Engineering and Mathematics Approach assisted by the phyphox application on circular motion material in order to improve the critical thinking skills of high school students. This research is adevelopment research (R&D) with the ADDIE model. This research uses a quantitative approach. The population of this study were students of class XI at SMA Muhammadiyah Maumere. The research sample was taken purposively, the sample numbered 25 people. The data collection technique was through a critical thinking ability test through an essay test.The data analysis techniques used are descriptive analysis and N-Gain test. This study produced a teaching material product in the form of LKPD which was declared valid based on expert assessment with an average of 92% material experts (very feasible) and 87% media experts (very feasible). LKPD is declared effective to use based on the results of the pretest and posttest of students' critical thinking skills through the N-gain test of 0.54 with moderate criteria. Based on the research results, it can be concluded that the product received a valid and effective assessment for use in physics learning at the high school level.